2015
DOI: 10.2106/jbjs.n.01208
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Triplane Ankle Fractures: Impact of Radiographs and Computed Tomography on Fracture Classification and Treatment Planning

Abstract: Computed tomography had a definite impact on the fracture classification, displacement, and treatment plan, supporting its use as an adjunct to radiographs for the treatment of pediatric triplane fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 34 publications
1
21
0
3
Order By: Relevance
“…The concern for radiation exposure has been previously addressed, and a standard ankle CT is estimated to be equivalent to the dose received by 0.9 chest radiographs [16]. Especially in fractures involving the joint surface, CT can provide invaluable information and has been shown to change surgical indications as well as surgical strategy [17][18][19][20]. MRIs of the ankle can provide further information to soft tissue structures about the ankle and the health of cartilage [21], but are often prohibitive in price and availability to achieve mainstream use in the treatment of acute ankle fractures.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The concern for radiation exposure has been previously addressed, and a standard ankle CT is estimated to be equivalent to the dose received by 0.9 chest radiographs [16]. Especially in fractures involving the joint surface, CT can provide invaluable information and has been shown to change surgical indications as well as surgical strategy [17][18][19][20]. MRIs of the ankle can provide further information to soft tissue structures about the ankle and the health of cartilage [21], but are often prohibitive in price and availability to achieve mainstream use in the treatment of acute ankle fractures.…”
Section: Imagingmentioning
confidence: 99%
“…The most significant recent development in pediatric ankle fractures has been the adoption of CT scanning as a routine procedure in triplane fractures. Through a 2015 study by Eismann et al, several qualified observers were asked to classify 25 triplane fractures with radiographs alone and then with CT scans on two separate occasions [19]. After reviewing tomography scans, raters changed the fracture pattern in 46% of ratings, the displacement from < 2 to > 2 mm in 39% of ratings, the treatment from non-operative to operative in 27% of ratings, and either the orientation or number of screws in 41% of ratings.…”
Section: Recent Developments and Future Directionsmentioning
confidence: 99%
“…21 Also, Eismann et al reported a Journal of Orthopaedic Surgery 28(3) significant rate of modification of the diagnosis after CT evaluation in pediatric triplane ankle fractures. 7 As misdiagnosis resulting in mismanagement of the fractures of the ankle causes an increased rate of morbidities, the aforementioned studies conclude that the evaluation of the ankle trauma patients with conventional radiography can cause misdiagnoses and the use of CT in ankle trauma is invaluable. ULDCT protocol used in this study having similar image quality with conventional CT can decrease the rate of misdiagnosis without increased radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Positive results following closed reduction of displaced triplane fractures with internal rotation and casting have been reported throughout the literature. Displaced transitional fractures with a fracture gap of more than 2 millimeters in the weight-bearing portion of the epiphysis require closed or open reduction [39,[48][49][50][51][52] .…”
Section: Editorialmentioning
confidence: 99%